Fenomena Hashtag #KaburAjaDulu : Maraknya Pemuda Indonesia yang Bekerja di Luar Negeri Analisis Sosial dan Ekonomi - Ella Riskhina Putri; Hafizh Siddiq; Sarah Diva Hairina Sinukaban; Putri Sosanti Sembiring (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The #KaburAjaDulu phenomenon illustrates a significant increase in the migration of young Indonesian laborers abroad in 2024–2025. This study employs a mixed-methods approach combining qualitative and quantitative methods to examine the social and economic factors driving migration, including domestic economic instability, low minimum wages, and unfavorable socio-political conditions. Data was collected through in-depth interviews and online surveys, then analyzed thematically and used descriptive statistics. The findings reveal that, in addition to economic factors, narratives of diaspora success and access to international opportunities also accelerate migration decisions. This phenomenon has dual implications: the potential for brain drain along with significant remittance contributions to the national economy. The study emphasizes the need for integrated policies to enhance employment opportunities and improve domestic socio-economic conditions to reduce the rate of young labor migration.